Urgensi Pembelajaran Pendidikan Agama Islam Berbasis Multikultural Di Sekolah - Muliadi, Erlan (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
The theology subject taught at the school tends merely to reinforce the faith and its achievements to go to heaven without consciousness for having a dialogue with other religions. These conditions make religious education very exclusive and intolerant. Whereas, nowadays pluralism era, religious education must be done the philosophical paradigmatic reorientation of how to make students understand about religion more inclusive, pluralistic, multicultural, humanistic, dialogue, persuasive, contextual, substantive, and socially active. Therefore, in this study emphasizes the importance of the development of multicultural education in schools through a number of Islamic religious education materials.